2013
DOI: 10.1080/02682621.2013.854544
|View full text |Cite
|
Sign up to set email alerts
|

Family focused grief therapy: a versatile intervention in palliative care and bereavement

Abstract: A diagnosis of advanced stage cancer is a difficult life event for the entire family. Previous studies have demonstrated the negative psychosocial outcomes associated with the burden of caregiving in conjunction with dysfunctional family relations. Family Focused Grief Therapy (FFGT) is a time-limited intervention that has been shown to be effective in aiding dysfunctional families through the promotion of family functioning, communication, cohesiveness, and conflict management. This paper outlines the content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Research shows that optimal bereavement support begins with significant others being a part of the dying process, and recognised as members of the health care team, regardless of their roles of responsibility and assistance in the care [ 2 , 33 ]. Empirical evidence shows that early intervention provided to a distressed family before the death of a terminally ill patient can ease their bereavement and reduce depressive symptoms [ 9 , 33 , 34 ]. A study of a support group programme for relatives during the late palliative phase revealed a sense of belonging, created by sharing similar experiences and not being alone [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that optimal bereavement support begins with significant others being a part of the dying process, and recognised as members of the health care team, regardless of their roles of responsibility and assistance in the care [ 2 , 33 ]. Empirical evidence shows that early intervention provided to a distressed family before the death of a terminally ill patient can ease their bereavement and reduce depressive symptoms [ 9 , 33 , 34 ]. A study of a support group programme for relatives during the late palliative phase revealed a sense of belonging, created by sharing similar experiences and not being alone [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRIG may seem to be a blunt assessment tool, only measuring “grief” or “severe grief” and not able to identify possible risk groups [ 37 ]. On the other hand, the HADS has been shown to be a valid scale measuring anxiety and depression separately, as originally suggested by its authors [ 27 , 33 ]. Still, both questionnaires are used worldwide, allowing valid comparisons to be made with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The family treatment led to greater distress reduction at follow‐up in individuals with high depression and distress scores at the baseline assessment (Kissane et al., ). Preliminary results from the second trial with a sample of 170 families showed that 6‐session or 10‐session FFGT could reduce the family members' depressive symptomatology compared to controls in a population of at‐risk families in which one member had cancer (Masterson, Schuler, & Kissane, ).…”
Section: Resultsmentioning
confidence: 99%
“…Neither the shared trauma literature nor grief work positions this commonality as an unequivocal problem; rather, the potential benefits for a therapist from an insider’s knowledge and experience of trauma are highlighted. In fact, some grief therapy protocols (e.g., Masterson et al ( 2013 ) family-focused grief therapy) foster a sense of shared loss. They ensure that the therapist is introduced to the person who will be mourned and the relationships impacted before the person's death so that the bereaved can process their grief with an expert who knows.…”
Section: Discussionmentioning
confidence: 99%